2002
DOI: 10.1046/j.1365-2168.2002.02125.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent popliteal fossa reflux following saphenopopliteal disconnection

Abstract: Despite preoperative duplex localization of the SPJ, SPD proved an unreliable technique in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 9 publications
1
65
0
6
Order By: Relevance
“…9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes. 10,11 It has been suggested that SSV surgery is more hazardous than GSV surgery, and that recurrence is more common. 4 Perioperative complication rates were low in the present series, as in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes. 10,11 It has been suggested that SSV surgery is more hazardous than GSV surgery, and that recurrence is more common. 4 Perioperative complication rates were low in the present series, as in other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rates as high as 49% have been described [11]. Labropoulos et al [12] have determined that SSV reflux was responsible for 29% of recurrent varices in the REVAS group.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the recurrences of SSV insufficiency have been attributed to inadequate (SPJ) dissection. Unligated branches, anatomical variations, and retained SSV have been commonly cited as an etiology [11]. …”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the literature indicates that outcomes after surgery for SSV are often suboptimal, with high rates of recurrence and a significant complication rate 2 -9 . Popliteal fossa anatomy is highly variable and, despite preoperative duplex marking, surgery is often technically inadequate, with an intact SPJ being reported in 24-47 per cent of patients at 6 weeks 3,5,8 . In one recent prospective multicentre observational study paraesthesia was present in 27 per cent of legs at 6 weeks, and in the majority this persisted after 12 months 3 .…”
Section: Discussionmentioning
confidence: 98%